National prospective study on the use of local haemostatic agents during partial nephrectomy. (31st October 2013) - Lang, Herve; Mouracade, Pascal; Gimel, Pierre; Bernhard, Jean C.; Pignot, Geraldine; Zini, Laurent; Crepel, Maxime; Rigaud, Jerome; Salomon, Laurent; Bellec, Laurent; Vaessen, Christophe; Roupret, Morgan; et al.
Abstract : Objective: To assess the use of local haemostatic agents (HAs) in a prospective multicentre large series of partial nephrectomies (PNs). Patients and Methods: Prospective National Observational Registry on the Practices of Haemostasis in Partial Nephrectomy (NEPHRON): the study was conducted in 54 French urological centres from 1 June to 31 December 2010. In all, 570 consecutive patients undergoing a PN were enrolled in this study in a prospective manner. The data was collected prospectively via an electronic case‐report form: five different sheets were included for preoperative, perioperative, postoperative and follow‐up data respectively. Information related to haemostasis was analysed. Results: The median patient age was 60 years and the mean (range) tumour size was 3.68 (0.19–15) cm. An HA was primarily used in 71.4% of patients, with a statistically significant difference among surgical approaches (P = 0.024). In 91.8% of cases, a single use of a HA was sufficient for achieving haemostasis. The HA was used either alone (13.9%) or in association with sutures (80.3%). One or more additional haemostatic action(s) was needed in 12.3% of the cases. When comparing patients who received a HA with those who did not receive a HA, there was no statistical difference between the groups for tumour size ( P = 0.542), collecting system drainage ( P = 0.538), hospital stay ( P = 0.508), operation time ( P = 0.169), blood loss ( P = 0.387) or transfusion rate ( P = 0.713). Conclusion: HAs are widely used by urologists during PN. Progress is needed for standardising HA application, especially for the timing of application. For the time being, the role of the HA in nephron‐sparing surgery is still to be evaluated.